Relationship between lysostaphin endopeptidase production and cell wall composition in Staphylococcus staphylolyticus. - Robinson, J M (1979)
Mutants of Staphylococcus staphylolyticus incapable of producing an extracellular staphylolytic glycylglycine endopeptidase were isolated and found to have cells in the population susceptible to lysis by this enzyme, as did the wild-type organism under conditions in which the endopeptidase was not produced. These results suggest that cultures of this organism normally contain a heterogeneous population of cells with regard to cell wall composition and susceptibility to the enzyme. Production of the endopeptidase appears to act as a selective pressure which removes the susceptible cells in the population as the enzyme appears in the medium. A comparison of the peptidoglycan of the wild-type organism grown under conditions in which the endopeptidase was produced with that of this organism grown under nonproducing conditions and with those of endopeptidase-less mutants showed that in the presence of the endopeptidase the cell population had peptidoglycan with shorter peptide cross bridges and a greater percentage of serine in these cross bridges than was found in cells grown in the absence of the enzyme. The inability of the endopeptidase to hydrolyze glycylserine and serylglycine peptide bonds suggests that at least part of the resistance this organism has to the endopeptidase is due to relative amounts of serine found in the peptide cross bridges of some cells in the population.